RNA-binding proteins with prion-like domains in health and disease - Harrison, Alice Ford; Shorter, James (Biochemical journal, 2017)
Approximately 70 human RNA-binding proteins (RBPs) contain a prion-like domain (PrLD). PrLDs are low-complexity domains that possess a similar amino acid composition to prion domains in yeast, which enable several proteins, including Sup35 and Rnq1, to form infectious conformers, termed prions. In humans, PrLDs contribute to RBP function and enable RBPs to undergo liquid-liquid phase transitions that underlie the biogenesis of various membraneless organelles. However, this activity appears to render RBPs prone to misfolding and aggregation connected to neurodegenerative disease. Indeed, numerous RBPs with PrLDs, including TDP-43 (transactivation response element DNA-binding protein 43), FUS (fused in sarcoma), TAF15 (TATA-binding protein-associated factor 15), EWSR1 (Ewing sarcoma breakpoint region 1), and heterogeneous nuclear ribonucleoproteins A1 and A2 (hnRNPA1 and hnRNPA2), have now been connected via pathology and genetics to the etiology of several neurodegenerative diseases, including amyotrophic lateral sclerosis, frontotemporal dementia, and multisystem proteinopathy. Here, we review the physiological and pathological roles of the most prominent RBPs with PrLDs. We also highlight the potential of protein disaggregases, including Hsp104, as a therapeutic strategy to combat the aberrant phase transitions of RBPs with PrLDs that likely underpin neurodegeneration.